2022
DOI: 10.3847/1538-4357/ac5027
|View full text |Cite
|
Sign up to set email alerts
|

On the Accuracy of Underground Muon Intensity Calculations

Abstract: Cosmic-ray muons detected by deep underground and underwater detectors have served as an information source on the high-energy cosmic-ray spectrum and hadronic interactions in air showers for almost a century. The theoretical interest in underground muons has nearly faded away because space-borne experiments probe the cosmic-ray spectrum more directly, and accelerators provide precise measurements of hadron yields. However, underground muons probe unique hadron interaction energies and phase space, which are s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In future iterations, we will employ the code mute [20,21] to further constrain the its parameters using a selection of muon measurements underground. In the contribution [21], we present that the underground data is well described by the present daemonflux.…”
Section: Discussionmentioning
confidence: 99%
“…In future iterations, we will employ the code mute [20,21] to further constrain the its parameters using a selection of muon measurements underground. In the contribution [21], we present that the underground data is well described by the present daemonflux.…”
Section: Discussionmentioning
confidence: 99%
“…The computational scheme of mute (v1.0.1) used for labs under flat overburdens is described in [1]. In this follow-up work, we introduce mute v2 [3], capable of calculating muon observables for laboratories beneath mountains.1 For the case of a flat overburden, symmetry in the azimuthal angle is assumed across all calculations, and there is a direct correspondence between slant depth, 𝑋, and zenith angle, 𝜃, for a given vertical depth ℎ:…”
Section: Methodsmentioning
confidence: 99%
“…mute (MUon inTensity codE) is a Python program that combines two state-of-the-art codes, mceq and proposal, to predict muon intensities and spectra in underground and underwater laboratories. Our previous work [1] has demonstrated the accuracy of mute in reproducing the measured vertical equivalent muon intensities within the models' uncertainties. Moreover, we have shown that the experimental uncertainties are smaller than the theoretical uncertainties, making the vertical-equivalent data an effective calibration source for high-energy neutrino flux calculations.…”
mentioning
confidence: 91%
See 1 more Smart Citation